The Exocyst Component Sec3 Controls Egg Chamber Development Through Notch During Drosophila Oogenesis - Wan, Ping; Zheng, Sumei; Chen, Lai; Wang, Dou; Liao, Ting; Yan, Xueming; Wang, Xiaoji (Frontiers in Physiology, 2019)
The exocyst complex plays multiple roles via tethering secretory or recycling vesicles to the plasma membrane. The previous studies have demonstrated that the exocyst contains eight components, which possibly have some redundant but distinct functions. Therefore, it will be interesting to investigate the biological function of each component. Here, we find that Sec3, one component of exocyst complex, is involved in Drosophila egg chamber development. Loss of sec3 results in egg chamber fusion through abolishing cell differentiation. In addition, loss of sec3 increases cell number but decreases cell size. These defects phenocopy Notch pathway inactivation. In line with this, loss of sec3 indeed leads to Notch protein accumulation, suggesting that loss of Sec3 inhibits the delivery of Notch onto the plasma membrane and accumulates inactive Notch in cytoplasm. Loss of sec3 also leads to ectopic expression of two Notch pathway target genes, Cut and FasciclinIII, which should be normally downregulated by Notch. Taken together, our studies reveal that Sec3 governs egg chamber development through regulating Notch, and provide fresh insights into the regulation of oogenesis.